2005
DOI: 10.1002/jcb.20421
|View full text |Cite
|
Sign up to set email alerts
|

A COMPASS in the voyage of defining the role of trithorax/MLL-containing complexes: Linking leukemogensis to covalent modifications of chromatin

Abstract: Chromosomal rearrangements and translocations play a major role in the pathogenesis of hematological malignancies. The trithorax-related mixed lineage leukemia (Mll ) gene located on chromosome 11 is rearranged in a variety of aggressive human B and T lymphoid tumors as well as acute myeloid leukemia (AML) in both children and adults. It was first demonstrated for the yeast MLL homolog complex, Set1/COMPASS, and now for the MLL complex itself, that these complexes are histone methyltransferases capable of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 47 publications
3
84
1
1
Order By: Relevance
“…This histone H3 modification in mammals is required for proper regulation of HOX gene expression. [26][27][28] The compositional and functional conservation between MLL and Set1 complexes establishes the existence of highly conserved, ancient molecular machinery for histone H3 methylation on K4 and emphasizes applicability of the yeast findings to the mammalian system.…”
Section: Regulation Of Histone Modifications By Bur1/bur2 Complexmentioning
confidence: 98%
“…This histone H3 modification in mammals is required for proper regulation of HOX gene expression. [26][27][28] The compositional and functional conservation between MLL and Set1 complexes establishes the existence of highly conserved, ancient molecular machinery for histone H3 methylation on K4 and emphasizes applicability of the yeast findings to the mammalian system.…”
Section: Regulation Of Histone Modifications By Bur1/bur2 Complexmentioning
confidence: 98%
“…The mechanistic basis for the initiation of these leukemias has not been definitively elucidated, but it appears to be related to the function of the protein product of the MLL gene. MLL, which is the human homolog of the Drosophila trithorax and yeast Set1 proteins, is a histone methyltransferase that is involved in transcriptional regulation in hematopoietic cells [94][95][96][97][98]. Accumulating evidence suggests that the fusion of the MLL protein with other cellular partner proteins alters enzyme function and affects the differentiation of pluripotent hematopoietic stem cells or committed myeloid or lymphoid stem cells by deregulating the expression of the HOX gene [94][95][96]98,99].…”
Section: Topoisomerase II As a Genotoxic Enzymementioning
confidence: 99%
“…Set1/KMT2 alone is not enzymatically active, but functions within COMPASS and is capable of mono-, di-, and trimethylating H3K4 [6,8,10,[24][25][26][27]. Following the identification of Set1/COMPASS as an H3K4 methylase, it was demonstrated that its mammalian homologues, the MLL proteins, MLL1-4 and hSet1A and B, are found in COMPASS-like complexes capable of methylating the fourth lysine of histone H3 [6,28,29] (Figure 2). While there is only one Set1 in yeast, there are over six Set1 related proteins in mammals, all capable of catalyzing the methylation of H3K4 (Figure 2).…”
Section: Enzymatic Machinery Required For H3k4 Methylationmentioning
confidence: 99%